Comparison of mortality between echinocandins and polyenes for an initial treatment of candidemia: A systematic review and meta-analysis. Issue 11 (November 2021) - Kato, Hideo; Hagihara, Mao; Shibata, Yuichi; Asai, Nobuhiro; Yamagishi, Yuka; Iwamoto, Takuya; Mikamo, Hiroshige
Abstract: Background: Current guidelines recommend echinocandins for the initial treatment of candidemia. However, polyenes are often chosen in clinical settings because of their fungicidal and anti -biofilm effects. Therefore, we performed a systematic review and meta-analysis to evaluate whether echinocandins are superior to polyenes in terms of mortality for the initial treatment of candidemia. Methods: We systematically searched the Scopus, EMBASE, Cochrane Central Register of Controlled Trials, PubMed, and CINAHL databases until July 1, 2020. We compared the mortality rates of patients who received echinocandins and polyenes. As a subgroup analysis, we compared the mortality rates following the use of echinocandins versus liposomal amphotericin B. Results: Fifteen studies involving 854 patients were included. Various Candida species were detected, and the rates of resistance of echinocandins and polyenes against the overall detected isolates were 1.0% and 0%, respectively. The overall mortality recorded in 15 studies was 41.0%, and the mortality was significantly higher for polyenes than echinocandins (odd ratios [OR] 1.68, 95% confidential interval [CI] 1.17–2.42). Furthermore, liposomal amphotericin B showed higher mortality in the initial treatment than echinocandins (OR 1.42; 95% CI 0.84–2.39). Conclusions: We revealed an association between echinocandin treatment and reduced mortality in the initial treatment of candidemia when causative fungi were not considered. Our findings partially support current guidelines recommending echinocandins for the treatment of candidemia.